Characterisation and genetic profiling of antibiotic resistance amongst Staphylococcus aureus and methicillin-resistant Staphylococcus aureus isolates from Selangor, Malaysia - Bitrus, Asinamai Athliamai (2017)
Staphylococcus aureus is a good model to illustrate the importance of gene transfer events in the global spread and dissemination of resistant clones worldwide. A total of 29 isolates (8 humans, 11 horses, 4 dogs, 4 chickens, 1 cat, and 1 from environmental surface) were used in this study. The isolates were reconfirmed as S. aureus using phenotypic and genotypic methods. Antibiotic susceptibility test was carried out using disk diffusion method. While screening of 10 selected virulence gene was carried out PCR. Mix liquid culture plating using graded doses of antibiotics was carried out to determine the in vitro transfer of methicillin resistant determinants mecA. PCR detection of SCCmec types and characterization of the universal attachment of SCCmec (orfX) and the SCCmec insertion site was carried out by PCR and Sanger’s sequencing and Molecular typing of the isolates was carried out using multilocus sequence typing (MLST) technique. The result of this study showed that, all isolates were nuc gene positive and (10/29) 34 % of the isolates were positive for mecA. While three (3/29) 10.34% isolates lack expression of mecA. There was a general reduction in the pattern of resistance to antibiotics previously tested. Reduced susceptibility was observed in two (2) isolates SDG2 and SH4 which were seen to be resistant to (8/13) 62% and (7/13) 54% of the antibiotics tested respectively. Resistance to amoxicillin, cefoxitin and oxacillin was also observed in (8/14) 57%, (9/14) 64% and (12/14) 86% of the MRSA isolates respectively. Four (4/14) 29% of the isolates were phenotypically resistant to vancomycin, doxycycline and amoxicillin-clauvulanic acid, while phenotypic resistance to tetracycline and erythromycin was also seen in (6/14) 43% and (5/14) 36% of the isolates respectively. Profiling of the virulence gene showed that a total of 20/29 (68.9%) and 14/29 (48%) of the isolates were positive for staphylococcus exotoxin-like toxin 1 (set1) and lipase encoding gene (geh). Also, twelve 11/29 (37%), and 7/29 (24.1%) of the all the isolates were positive for beta hemolysin (hlβ) and V8 protease (SspA) respectively. The isolates were also positive for exfoliative A (etA) 2/29 (6.9%), alpha hemolysin (hlα) 2/29 (6.9%) and staphylococcus enterotoxin u (Seu) 4/29 (13.8%). Additionally, a total of 5/29 (17.2%) and 3/29 (10.34%) of the isolates were positive for phage-borne Panton valentine leukocidine (PVL) and exfoliative toxin B. While only 1/29 (3.4%) of the isolates was positive for gene coding for toxic shock syndrome toxin-1 (tst). The result of the antibiogram revealed a reduced susceptibility and multidrug resistance in four isolates (and susceptibility to all antibiotics observed in two isolates. The findings of the in vitro transfer of mecA gene using mix liquid culture plating on Luria-Bertini (LB) agar each separately containing antibiotics 100 μg/mL, 50 μg/mL and 30 μg/mL of erythromycin and cefpodoxime for selection of donor cells, tigecycline and levofloxacin for selection of recipient transconjugants showed that transfer of resistance determinants occurred between MRSA to MSSA. Screening of SCCmec types showed that majority of the MRSA isolates carried SCCmec typing III 7/11(63%). While only 3/11 (27%) and 1/11 (9.0%) of the isolates were positive for SCCmec type II and IVe. PCR amplification of the universal insertion site of the SCCmec (orfX) and attachment site showed that all the isolates 16/16(100%) were positive for the orfX gene while 7/16(43.8%) were positive for the attB. In addition, phylogenetic tree analysis using Maximum Likelihood method showed that the isolates demonstrate a significant level of diversity. Multilocus sequence typing (MLST) analysis revealed two types of sequence types (STs) ST1 and ST177.The findings of this study showed the effect of prolonged storage temperatures on resistance gene, the carriage of virulence genes and demonstrate the transfer of methicillin resistance genes. Additionally, SCCmec types were screened, its insertion site characterised and finally, the clonal types in a collection of S. aureus isolates was determined. Hence, providing baseline data on the global spread of resistance and virulence genes as well as transmission of MRSA from humans to animals.